2019
DOI: 10.3390/ijerph16203868
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Bacterial Communities in Response to Prolonged Hydrodynamic Disturbances in the Eutrophic Water-Sediment Systems

Abstract: The effects of hydrodynamic disturbances on the bacterial communities in eutrophic aquatic environments remain poorly understood, despite their importance to ecological evaluation and remediation. This study investigated the evolution of bacterial communities in the water–sediment systems under the influence of three typical velocity conditions with the timescale of 5 weeks. The results demonstrated that higher bacterial diversity and notable differences were detected in sediment compared to water using the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The predominance of Proteobacteria across all examined locations aligns with the existing literature, which often cites Proteobacteria as a dominant phylum in aquatic environments [32][33][34]. This ubiquity can be attributed to the diverse metabolic capabilities of Proteobacteria, allowing them to thrive in various environmental conditions.…”
Section: Discussionsupporting
confidence: 85%
“…The predominance of Proteobacteria across all examined locations aligns with the existing literature, which often cites Proteobacteria as a dominant phylum in aquatic environments [32][33][34]. This ubiquity can be attributed to the diverse metabolic capabilities of Proteobacteria, allowing them to thrive in various environmental conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, some studies have reported that bacterial communities sampled from water bodies presented considerable spatiotemporal variation since the stream makes these environments more dynamic [60,61]. Alternatively, recent studies have revealed that the diversity and structure of sediment bacterial communities are not affected by space-time variations [19,[24][25][26]. This evidence has shown that the use of a water body as a sampling matrix tends to generate a more reliable diagnosis of the diversity and structure of bacterial communities in a more restricted temporal frame, whereas sediment analyses are more suitable when the main goal is to identify chronic impacts on freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the matrices available in river environments to sampling, recent studies have shown that bacterial communities from water and sediment are distinct components of aquatic ecosystems (a stream tends to create a more dynamic environment for water), of which the bacterial diversity in sediments is considerably higher and more suitable to predict chronic environmental disturbances caused by human activities than water bacterial communities [21][22][23][24][25][26]. Recent evidence has revealed that during the intensification of landuse processes, contaminants are absorbed by the fine particles of sediments and interact with local bacterial communities, causing long-term impacts on the biological organization of the communities and leading to changes in both the diversity and composition of the bacterial communities [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et al ( 2022 ) found that changes in surface hydrological conditions can lead to differences in microbial community structure and dominant groups, such as the increase of Actinobacteria due to low water volume, thus affecting the metabolic activity of microbial communities. Complex hydrological conditions can also affect the composition and potential functional trends of microbial communities (Cheng et al, 2019 ). Arnon et al ( 2007 ) found that the high flow rate conditions can promote the transfer of chemical substances between water and sediment, provide nutrients for microorganisms, and promote the denitrification process.…”
Section: Introductionmentioning
confidence: 99%